2001
DOI: 10.1076/phbi.39.1.67.5944
|View full text |Cite
|
Sign up to set email alerts
|

The Medicinal Value of Tropical Rainforest Plants from Paluma, North Queensland, Australia

Abstract: A pharmacological survey of flora of the Paluma rainforest including 90 species representing 19 families has been carried out. Crude plant extracts have been screened for cytotoxic, antibacterial, antifungal, and antiviral activity, as well as brine shrimp lethality. Of these, 27 extracts exhibited remarkable cytotoxic activity, 23 showed antimicrobial activity, and 7 showed promising antiviral activity. Thus, 53 of the plant species examined showed marked bioactivity in one or more bioassays; a "hit rate" of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 11 publications
0
48
0
1
Order By: Relevance
“…One study has reported low toxicity of other Syzygium species (S. endophoium, S. johnsonii, S. papyraceum, S. wesa) against HepG2, and two carcinoma cell lines. [36] The same study reported more complex toxicity results for S. wilsonii extracts. S. wilsonii extracts also displayed low toxicity towards HepG2 and a breast carcinoma cell line but showed substantial toxicity towards a bladder carcinoma cell line.…”
Section: Resultsmentioning
confidence: 89%
“…One study has reported low toxicity of other Syzygium species (S. endophoium, S. johnsonii, S. papyraceum, S. wesa) against HepG2, and two carcinoma cell lines. [36] The same study reported more complex toxicity results for S. wilsonii extracts. S. wilsonii extracts also displayed low toxicity towards HepG2 and a breast carcinoma cell line but showed substantial toxicity towards a bladder carcinoma cell line.…”
Section: Resultsmentioning
confidence: 89%
“…The ability of K. africana fruit extracts to inhibit the growth of both Gram-positive and Gramnegative bacteria is in agreement with previous reports of the antibacterial activity of other plants that have a history of medicinal usage in traditional healing systems. [41][42][43][44] The current study shows Gram-positive and Gramnegative bacteria to be approximately equally susceptible to the K. africana fruit extracts. This is in contrast to previous studies which have reported a greater susceptibility of Gram-positive bacteria towards solvent extracts for South American, [45] African, [46] and Australian [47] plant extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The lethal concentration for 50% mortality after 24 hours of exposure, the chronic LC50 and 95% confidence intervals were determined by using the Probit method as the measure of toxicity of the extract or fractions. The extracts were considered as toxic at LC 50 less than 10 µg/ml (Setzer et al, 2001 …”
Section: Brine Shrimp Lethality Testmentioning
confidence: 99%